Financial Technology: The Promise of Blockchain - Markus Demary; Vera Demary (Institut der deutschen Wirtschaft (IW), 2017)
Digitization affects all sectors of the economy. A new and possibly disruptive digital technology is the blockchain, a decentralized ledger, which seems to offer great promise for many financial and business applications.
Keywords: 330